Finnish flies of the family Therevidae - Haarto, Antti; Winqvist, Kaj (Entomologica Fennica, 2006)
An illustrated key for the 17 Finnish species of Therevidae is presented that includes six species recorded from neighbouring areas. Distributions of the Finnish species are discussed and presented in maps; evaluations concerning the threatenedness status of Finnish species are included.